Review of neoadjuvant chemotherapy and trachelectomy: which cervical cancer patients would be suitable for neoadjuvant chemotherapy followed by fertility-sparing surgery? - Robova, Helena; Rob, Lukas; Halaska, Michael Jiri; Pluta, Marek; Skapa, Petr (Current oncology reports, 2015)
The number of patients given neoadjuvant chemotherapy (NAC) followed by fertility-sparing surgery in cervical cancer is still scarce. Only a few centres perform these procedures, and thus, such procedures remain largely in the experimental stage. Patients that do not fulfil the criteria for standard fertility-sparing procedure can be included in studies with NAC followed by fertility-sparing procedure. We must consider that both oncological and pregnancy outcomes are important. Patients with only microscopic disease after NAC are apparently the best candidates for fertility-sparing surgery. Current data are not sufficient to identify the optimal procedure after NAC [abdominal radical trachelectomy (ART) or vaginal radical trachelectomy (VRT) or simple trachelectomy]. Some evidence suggests that pregnancy outcome is better after simple trachelectomy as compared with VRT or ART. Long-term results regarding oncological outcome for this concept are still lacking. Adjuvant chemotherapy in patients with histopathological risk factors (lymphovascular space involvement (LVSI), macroscopic residual disease) would decrease a risk of recurrence.
Keywords: Gynecologic Surgical Procedures; Neoadjuvant Therapy; spinocelulární karcinom; těhotenství; Sentinel Lymph Node Biopsy; výsledek terapie; výsledek těhotenství; Neoplasm Recurrence, Local; Adult; lokální recidiva nádoru; zachování plodnosti; nádory děložního čípku; kombinovaná terapie; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; Humans; Pregnancy; Pregnancy Outcome; gynekologické chirurgické výkony; neoadjuvantní terapie; Antineoplastic Combined Chemotherapy Protocols; Combined Modality Therapy; Uterine Cervical Neoplasms; protokoly protinádorové kombinované chemoterapie; dospělí; Carcinoma, Squamous Cell; biopsie sentinelové lymfatické uzliny; Female; Treatment Outcome; lidé; Fertility Preservation